Tulodziecki brothers – tribute to biography - Dobrzeniecka, Monika (Saeculum Christianum. Pismo Historyczne, 2021)
The aim of the article is to portray the heroes of Sierpc from the first half of the 20th century: Henry, Edward and Felician Tulodziecki. It comprises a synopsis of their activity in the fields of education and politics, including their participation in the organisational units of the Polish Socialist Party.